Ability of a Combined FIB4/miRNA181a Score to Predict Significant Liver Fibrosis in NAFLD Patients - Rodrigo Vieira Costa Lima; José Tadeu Stefano; Fernanda de Mello Malta; João Renato Rebello Pinho; Flair José Carrilho; Marco Arrese; Claudia P. Oliveira (Biomedicines, 2021)
Liver biopsy is the gold standard for assessing fibrosis, but there is a need to seek non-invasive biomarkers for this purpose. The aim of this study was to evaluate the correlation between the serum levels of the microRNAs miR-21, miR-29a, miR-122, miR-155 and miR-181a and the phenotypic expression of NAFLD. A cross-sectional study was carried out on 108 NAFLD patients diagnosed by liver biopsy. FIB-4 and NAFLD fibrosis scores were calculated. The comparison between the distributions of microRNA values according to the presence or absence of histological fibrosis (F2–F4) was performed. A multivariate logistic regression analysis was performed to build a score for predicting fibrosis using FIB-4 and Ln (miR-181a) as independent variables. Only miR-181a showed a statistical difference between patients with significant liver fibrosis (>F2) and those without (F0–F1) (p = 0.017). FIB-4 revealed an AUC on the ROC curve of 0.667 to predict clinically significant fibrosis (F2–F4). When assessed using the score in association with Ln (miR-181a), there was an improvement in the ROC curve, with an AUC of 0.71. miR-181a can be used as a non-invasive method of predicting fibrosis in NAFLD, and an association with FIB-4 has the potential to increase the accuracy of each method alone.